Fabrication and evolution of catalyst-coated membranes by direct spray deposition of catalyst ink onto Nafion membrane at high temperature - Sun, L.; Ran, R.; Shao, Zongping (Elsevier Ltd, 2010)
An improved fabrication technique for catalyst-coated membrane (CCM), characterized by high-temperature spray deposition and immobilization of the membrane with a pyrex glass via Van der Walt force, was developed. The high heating temperature minimized the adsorption of liquid ethanol by the Nafion membrane and also resulted in the firm adhesion of the membrane to the pyrex glass, both processes suppressed the dimensional change of the membrane during the fabrication. The as-fabricated CCMs were analyzed by I-V polarization, cyclic voltammetry and electrochemical impedance spectroscopy. A comparative study was also made with the conventional hot-pressed membrane-electrode assembly with identical Pt catalyst loading of 0.4 mg cm-2. Higher catalyst utilization and better cell performance were observed for the cell based on the CCM configuration. A peak power density of ~715 mW cm-2 was achieved when oxygen was the cathode atmosphere and hydrogen was the fuel at ambient pressure. © 2009 Professor T. Nejat Veziroglu.